2017
DOI: 10.3390/polym9100464
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Electrospun Polylactic Acid/Cinnamaldehyde/β-Cyclodextrin Fibers as an Antimicrobial Wound Dressing

Abstract: Cinnamaldehyde (CA) was successfully encapsulated in β-cyclodextrin (β-CD), and polylactic acid (PLA)-based composite fibers were prepared by incorporating CA/β-CD via electrospinning. Morphological, structural, spectral, and antibacterial properties of different weight ratios of PLA:β-CD/CA (88:12, 94:6, 97:3, and 98.5:1.5) and PLA/CA/β-CD fibers were investigated. PLA and CA/β-CD were incorporated by mixing of CA/β-CD inclusions to enhance the viscosity of the mixed solution. The mechanical properties and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 45 publications
0
59
0
Order By: Relevance
“…Although, silver (Ag) nanoparticles have been blended into electrospun zein fibers to achieve antibacterial properties, [ 25 ] it is believed that use of natural medicinal extracts such as essential oils can further boost pharmaceutical applications and in vivo patient care due to their low toxicity and broad spectrum antimicrobial activities. [ 26–32 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although, silver (Ag) nanoparticles have been blended into electrospun zein fibers to achieve antibacterial properties, [ 25 ] it is believed that use of natural medicinal extracts such as essential oils can further boost pharmaceutical applications and in vivo patient care due to their low toxicity and broad spectrum antimicrobial activities. [ 26–32 ]…”
Section: Introductionmentioning
confidence: 99%
“…33 However, cinnamaldehyde has certain shelf-life problems due to its high volatility, low stability, low solubility, and sensitivity to oxygen, light, and heat. 34,35 Yet, molecular encapsulation of cinnamaldehyde with cyclodextrin inclusion complexation is one of the promising approaches in order to eliminate the abovementioned drawbacks of cinnamaldehyde. For example, it was shown that enhancement of photostability and thermostability of cinnamaldehyde after complexation with γ-CD derivatives was possible.…”
Section: ■ Introductionmentioning
confidence: 99%
“…35,40,41 For instance, cinnamaldehyde/β-CD-ICincorporated polylactic acid (PLA) nanofibrous mat was fabricated as a potential candidate for the use of wound dressing material due to its antibacterial properties and low cytotoxicity. 35 Also, a polyvinyl alcohol/cinnamon essential oil/β-CD-IC nanofibrous film was fabricated by electrospinning for active food packaging by increasing the hightemperature stability of cinnamon essential oil by inclusion complexation and prolonging the shelf life of strawberries by showing effective antimicrobial activity. 40 Also, cinnamon essential oil/β-CD-IC was incorporated into electrospun PLA NFs for antimicrobial packaging application in which the PLA/ cinnamon essential oil/β-CD nanofibrous film has shown better antimicrobial activity compared to PLA/cinnamon essential oil nanofibrous film.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Biocompatible materials play a more and more important role in tissue engineering [9], medicine delivery [10], antibacterial application [11], and wound healing [12]. Among them, synthetic polymer materials are very popular in the skin regeneration [13,14]. As one of the synthetic polymers, Poly-l-lactic acid (PLLA) with controlled degradation has been studied in clinic medicine for a long time [15].…”
Section: Introductionmentioning
confidence: 99%